The effect of drying temperature on the characteristics of biodegradable plastic from Cassava pulp and Chitosan - Adina Widi Astuti; Agus Yulianto; Upik Nurbaiti (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
Conventional plastics made from polyethylene (PE), polypropylene (PP), polyvinylchloride (PVC), polystyrene, and poly (ethylene terephthalate) are difficult to decompose. Bioplastics can reduce the amount of toxic waste generated from biological materials other than petroleum. The combination of cassava pulp and chitosan can be used as a candidate for the manufacture of biodegradable plastics. The optimal drying temperature can produce biodegradable plastics that have good quality. The method used to determine the effect is the mechanical properties test with ASTM D-638M standard and degradation test. The results of this study obtained 6 samples of biodegradable plastic with variations in temperature A=40˚C, B=50˚C, C=60˚C, D=70˚C, E=80˚C and F=90˚C. From the results of the mechanical properties test, the tensile strength values of each sample are A = 0,84 MPa, B = 1,78 MPa, C = 2,24 MPa, D = 1,58 MPa, E = 1,23 MPa and F =0,57 MPa. While the percent elongation value of each sample is A = 11,09%, B = 21,62%, C = 30,25%, D = 15,94%, E = 13% and F = 7,2%. The drying temperature in the process of making biodegradable plastics can affect its mechanical properties, namely the higher the drying temperature used, the lower the tensile strength value and the percent elongation, this is because high temperatures can damage the chemical structure and evaporated sorbitol which serves to increase flexibility. The higher the drying temperature also causes the biodegradable plastic to take longer to degrade. Sample A with the lowest temperature degraded the fastest for 28 days, while sample F with the highest temperature degraded the fastest for 46 days.©2021 JNSMR UIN Walisongo. All rights reserved.